THE INFLUENCE OF SOCIODEMOGRAPHIC FACTORS ON THE DEVELOPMENT OF ANXIETY A CORONAVIRUS DISEASE PANDEMIC - Jandric-Kocic, Marijana; Knezevic, Snezana (HEALTH CARE, 2020)
Introduction/Aim: The COVID-19 pandemic poses a serious threat to global mental health. Fear of death, social distancing, economic problems, changes in the education system, and cessation of normal daily functioning induce psychiatric disorders, primarily anxiety. The research aimed to determine the influence of sociodemographic factors on the development of anxiety during the COVID-19 pandemic. Methods: The cross-sectional study, over two months, included 200 persons without symptoms of COVID-19, 60.0% of women and 40.0% of men, with an average age of 51.0 ± 9.2 years. One hundred people reported to the family medicine clinic of the Health Care Center Krupa on the River Una for examinations or administrative reasons, and another hundred were accompanied by them. In addition to the general questionnaire, the Generalized Anxiety Disorder-7 (GAD-7) Self-Assessment Symptom Intensity Questionnaire was used. The χ2- test and Fisher’s test were used for the statistical analysis. Discussion: 105 (52.5%) participants included in the study had symptoms of anxiety (35.0% mild symptoms of anxiety, 15.5% moderate symptoms of anxiety, 2.0% severe symptoms of anxiety). Anxiety was slightly more common in men (56.2%) than in women (50.0%), as well as in the oldest (60-79 years) (92.6%) than in younger participants (12.5% for age 20-39 and 44.7% for ages 40-59). The frequency of anxiety was lower in persons with higher (33.3%) than lower education (44.5% of participants with primary and 46.6% of participants with high school). A slightly higher frequency of anxiety was among the employed (69.5%) than among the unemployed (43.0%), as well as among persons living in urban (80.8%) in comparison to those living in rural (42.6%) areas. Anxiety problems were experienced by 51.3% of participants living in marriage or extramarital union and 56.8% of participants who were not married or in an extramarital union. People with anxiety were significantly more likely to be aged 60-79 than people without anxiety. There were no significant differences between these groups in terms of gender, level of education, employment, place of residence and marital status of the participants. Conclusion: Every other person in this study had some form of anxiety. Further research in this area and proposing adequate prevention programs are needed.